Manajemen Anestesi Operasi Total Thyroidectomy Pada Pasien Struma Multinodosa: Laporan Kasus - Aqsha Madina; Anna Millizia (Jurnal Anestesi, 2024)
Goiter is an enlargement that occurs in the thyroid gland. Goiter can be classified based on physiology (euthyroidism, hypothyroidism, and hyperthyroisdism), morphology (diffuse and nodular goiter) and clinically (toxic and non-toxic goiter). Multinodular goiter is an enlargement of the thyroid gland with multiple nodules in which the thyroid gland follicles experience changes both morphologically and functionally. The characteristics of nontoxic multinodose goiter are slow, continuous and expanding growth. Surgery is one treatment for most types of goiter. The operation is performed under general anesthesia. Operative procedures performed on the head and neck are high-risk operations that can cause brain damage and result in death. Therefore, it’s necessary to prepare an anesthesia plan as well as appropriate pre-operative, intra-operative and post-operative management to avoid complications that may occur. Mrs. BP, 65 years old, came with complaints that a lump had appeared in his neck since approximately 2 years ago and had grown to approximately 5 cm in the last 1 year. In 2003 the patient underwent partial thyroidectomy under general anesthesia. This case report aims to look at anesthetic management in patients with multinodose goiter, where appropriate anesthetic management also determines the success and prognosis of surgical procedures in these patients.